The Effect of Formula Feedings Compared to Exclusive Breastfeeding on KPSP Screening Aged 0-6 Months at Kebayoran Baru Health Center. - Kunarisasi, Sity; Susianti, Yanti; ZD, El Izhar (Journal of Health Science and Prevention, 2024)
Introduction: In the world, the rate of newborns receiving early initiation of breastfeeding (IMD) is still low at around 47% and 44% of infants aged 0-6 months are receiving exclusive breastfeed, in Indonesia in 2023 it increased compared to 2022 by 1.93 %. Similarly, the state DKI Jakarta grew by 9.17 % in 2023 compared to in 2022. The recommendation of the Ministry of Health, Indonesia that progress monitoring through SDIDTK using the Pre-Screening Developmental Questionnaire (KPSP) instrument is a health service to monitor the development of infant growth and development in improving the quality of life. Thus, this study, know the difference in development between exclusively breastfed babies and formula milk babies. Methods: observational and analytic. Samples of infants 0-6 months using KPSP (gross motor, fine motor, speech and language, socialization and independence) to determine the development of infants at the Kebayoran Baru Health Center, Jakarta. Results: The Mann-Whitney test obtained a p-value of 0.078 (>0.05) found no significance between the development of exclusively breastfed infants and formula infants. Conclusion: The results of KPSP are not different, so it is necessary to consider the influence of internal and external factors.